Self-Efficacy in Kampus Mengajar: Implication for Preservice Teacher's Education - Chusnul Chotimah, Ima; Karesta Haris Prastiwa; Dian Anik Cahyani (Penerbit STKIP PGRI Bangkalan, 2024)
The Kampus Mengajar program is one of the government programs in which college students from all over Indonesia can participate. The placement of the Kampus Mengajar program is in marginal schools that are lagging in elementary and junior high schools. Students are expected to serve in these schools as help staff. Therefore, self-efficacy is important to support their ability to complete their assignments. This study aimed to determine students’ self-efficacy in the Kampus Mengajar program in English Department STKIP PGRI Jombang. This study adapted the three dimensions of self-efficacy from Bandura's theory, namely the level dimension, generalization dimension, and strength dimension. The respondents of this study were students majoring in English from STKIP PGRI Jombang who took part in the Kampus Mengajar program batch 3. There are 8 of them and they take part in the Kampus Mengajar program in semester 5. A qualitative case study was used in this research. The research instruments are questionnaires and interviews to get accurate results. The type of questionnaire used was a closed-ended questionnaire and the results were strengthened by the interview process. The results show that the respondents have self-efficacy to carry out the assignment in the Kampus Mengajar placement school program.